Telenursing and self-management among patient with hypertension - Sri Sakinah; Sulkifli Nurdin (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: Hypertension is still a risk factor for the leading cause of death in the world. Hypertension is a blood pressure condition of more than 140/90 mmHg. Patient with hypertension who are an uncontrolled their blood pressure and the number continues to increase, one of which is through services nursing. Nurses are one of the health professions involved in achieving health development goals both in the world and in Indonesia. Health information technology is increasingly developing which must be of concern, especially in the world of nursing to help answer health problems public through telenursing which was developed by providing telecommunications assistance via WhatsApp. Purpose: To determine the effect of telenursing and self-management among patient with hypertensionMethod: This study was conducted in June - August 2020 with a method quasi experimental pre and post test with control group (giving treatment telenursing via WhatsApp to the intervention group and control group using the media short message service (SMS). The sample in this study were all patients with hypertension in accordance with the inclusion criteria (hypertensive patients who undergo treatment, have android, and are able to read and write) The media used in this study were cell phones Results: Through the Paired Sample Test it is known that the p value in thegroup is controlled SMS based on systolic blood pressure was 0.008 (<0.05), while in the intervention group the WA p value was 0.001 (<0.05). This shows a significant result, but the researchers considered that the intervention group had a more significant value when compared to the control. Likewise, the diastolic blood pressure in which the control group was obtained p-value 0.051 (> 0.05) while the intervention group obtained p value of 0.000 (<0.05). Conclusion: There was no significant difference in blood pressure in the group, control use media short message service (SMS). While the intervention group showed a very significant difference between before and after telenursing used media WhatsApp